UbiWheel: A simple context-Aware universal control concept for smart home appliances that encourages active living - Sandnes, Frode Eika; Herstad, Jo; Stangeland, Andrea Marie; Medola, Fausto Orsi [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Smart homes contain many useful appliances that can help individuals live independently for longer. A problem with current smart homes prototypes is that each device often has its own remote control or control unit. These control units are often manufactured by different suppliers with totally different and inconsistent user interfaces. This is confusing for most individuals and become a huge barrier for individuals with reduced cognitive function. This paper thus introduces a conceptual sketch of a universal and ubiquitous control wheel, termed UbiWheel that is designed to control most appliances in the home. The user simply moves the controller to the proximity of the device be controlled and adjust parameters by simply twisting the wheel, thereby preventing inactivity as the user need to move around the home. Several cases are explored herein.
Keywords: context-Awareness; smart home; universal remote